Incorporation Of Banana Peel Fiber In Jelly As A Functional Food Precursor - Radzi, Hilma Aini Md (Universiti Sains Malaysia, 2020)
The peel of banana was evaluated for the potential to be utilized as dietary fiber for functional food. The main objectives of this study were to develop banana peel fiber jelly by incorporating the banana peel fiber extract in the jelly formulation, to determine total dietary fiber content, texture properties and syneresis of produced fiber-added jelly. Banana peel powder was treated with the enzymatic-gravimetric method to extract the fiber powder from banana peel prior to drying and grinding treatments. Obtained banana peel fiber powder was incorporated into the jelly with two different ratios (5 and 10%) to produce jelly from fruit wastes with high fiber content. Both jelly samples including jelly sample with 5% banana peel fiber added and jelly with 10% banana peel fiber added were undergone total dietary fiber (TDF), texture and syneresis analysis. The increasing amount of banana peel incorporated into jelly had significantly increased (p<0.05) in TDF of jelly samples. For texture properties, it was found that the concentration of banana peel fiber had a significant effect on the texture properties of the jelly. An increase the fiber content caused a significant difference (p<0.05) in hardness, adhesiveness, cohesiveness, springiness and chewiness except for the other parameter which is gumminess was not significantly affected (p>0.05). Fiber-added jelly made with 10% banana peel fiber extract had significantly decreased (p<0.05) in syneresis values for both of refrigerated storage time. In summary, peel of banana used in this study had a great potential to be used as the functional ingredients for dietary fiber addition in the jelly. Both banana peel jellies were safe for consumption.